Examining Jakarta office mosques: Islamic teaching practices and views of Islamic ideological issues - Ridwan Al-Makassary (Indonesian Journal of Islam and Muslim Societies, 2013)
This paper discusses Islamic teaching practices and perceptions of mosque stake-holders concerning the ideological issues of: a democratic system of governmentversus formal implementation of Islamic sharia; gender equality; jihad, and plu-ralism in the Jakarta office mosques. After describing the research findings, thepaper concludes that the phenomenon of neo-fundamentalism (in Olivier Roy’swords) is growing and developing in office mosques. This can be seen in thedominance of literal and scripturalist Islamic interpretations, the importance givento implementing Islamic sharia and the rejection of democracy, a hatred of Jewsand Christians and the emergence of Muslim youth actors in Islamic neo-fundamentalism. Other findings concern the influence of the Tarbiyah movement, anoffshoot of the Ikhwanul Muslimin (Muslim Brotherhood), which is being felt inthe office mosques studied. Learning about Islamist understandings will allow usto check its development, which may destroy the friendly, peaceful face of Islam.Paper  ini  mendiskusikan  praktik  pengajaran  Islam  dan  persepsi  pemangkukepentingan  masjid  berkaitan  dengan  isu-isu  ideologis:  sebuah  sistempemerintahan demokratik versus implementasi formal syari’at Islam; kesetaraanjender; jihad, dan pluralism di masjid perkantoran Jakarta. Setelah deskripsitemuan  penelitian,  paper  ini  menyimpulkan  bahwa  fenomena  neo-fundamentalisme (meminjam Olivier Roy) sedang tumbuh dan berkembang dimasjid-masjid perkantoran. Ini terlihat dari dominannya intepretasi skripturaldan literal, pentingnya menerima pelaksanaan formal syari’at Islam, kebencianterhadap Yahudi dan Kristen dan kebangkitan aktor-aktor muda fundamentalismeIslam. Temuan lain terkait dengan gerakan Tarbiyah, sebuah anak ideologi IkhwanulMuslimin (Muslim Brotherhood), yang cukup kental ditemukan di masjid yangditeliti.  Mengkaji  pemahaman  Islam  akan  memungkinkan  kita  mengawasiperkembangannya, yang mungkin menghancurkan wajah Islam yang ramah dandamai.